1986
DOI: 10.1111/j.1365-2621.1986.tb13133.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Fatty Acid, and Oil Characteristics of Pumpkin and Melon Seeds

Abstract: Nutritional and oil characteristics of pumpkin and melon seeds were investigated. On a dry basis, the data obtained for the two seeds, respectively, were: crude oil 45.4 and 37.8%; crude protein, 32.3 and 25.2%; crude fiber, 12.1 and 15.4%; and ash, 4.65 and 3.85%. Food energy values were 2.83 and 2.59 MJ/lOOg, respectively. The seeds were found to have considerable amounts of essential minerals (K, Ca, Mg, Fe, Cu, Zn, and P). The defatted flour of the pumpkin and melon seeds contained, respectively: crude pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
1
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 6 publications
8
69
1
2
Order By: Relevance
“…y calabaza (Cucurbita spp.). Lazos, 1986), the percentage of linoleic acid was lower (43.1-55.6%) than that found in pumpkin in this study (63.11-69.12%). It is important to point out that the variability in the composition of fatty acids regarding to other studies is probably due to a diversity of factors such as variety, cultivation area, climate, and degree of ripeness (Murkovic, Hillebrand, Draxl, Winkler, & Pfannhauser, 1999).…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…y calabaza (Cucurbita spp.). Lazos, 1986), the percentage of linoleic acid was lower (43.1-55.6%) than that found in pumpkin in this study (63.11-69.12%). It is important to point out that the variability in the composition of fatty acids regarding to other studies is probably due to a diversity of factors such as variety, cultivation area, climate, and degree of ripeness (Murkovic, Hillebrand, Draxl, Winkler, & Pfannhauser, 1999).…”
Section: Resultscontrasting
confidence: 48%
“…Several studies have reported about the chemical composition and characteristics of seed oil from pumpkin and mamey (Lazos, 1986;Stevenson et al, 2007). The main fatty acids identified in pumpkin seed oil were palmitic, stearic, oleic, and linoleic acids (Gohari-Ardabili et al, 2011;Stevenson et al, 2007), while in mamey seed oil, these were oleic, stearic, palmitic, palmitoleic, and linoleic acids (Solı´s-Fuentes & Dura´n-de-Bazu´a, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical characteristics of various cucurbit seed oils as well as work on edibility and stability have been reported (2,4,6,7). The oil content of various cucurbit seeds varied from 38 to 60% (3,4,8).…”
Section: Introductionmentioning
confidence: 99%
“…Pumpkin seed oil has a special place among edible oils produced in Yugoslavia, while large quantities of this oil are produced in Austria, Hungary and southern parts of the former USSR (3). In Greece, no oil or protein from such seeds has been produced, but pumpkin seeds are consumed in significant amounts as a snack in the form of salted roasted seeds, constituting a food rich in oil and protein (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Pumpkin seeds are rich in protein (25.2-37%) (Lazos 1986). The main storage proteins are salt-soluble globulins, accompanied by glutelins and lesser amounts of albumins and prolamins (Marcone 1997).…”
Section: Resultsmentioning
confidence: 99%